Secondary School Teachers’ Accessibility to Internet Facilities for Advanced Instruction in Nigeria - Adenike Aderogba Onojah; Amos Ochayi Onojah; Charles Olubode Olumorin; Esther O. Omosewo (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2021)
For internet facilities to be adopted and integrated in schools, the resources should not only be available, it must also be accessible. The objectives of this study were to: identify internet facilities available for second-ary school teachers; determine whether secondary school teachers are able to access the internet facilities; and investigate how teachers’ gender influence the accessibility of internet facilities in secondary schools in Ilorin. The population of the study was limited to secondary school teachers in Ilorin, Nigeria and 251 re-spondents were randomly selected. There was no significant difference between male and female secondary school teachers’ level of accessibility of internet facilities for instruction. The study concluded that teachers have access to the available internet facilities for advanced instruction. It was recommended that, Internet Service Providers (ISPs) should be allowed to establish centres on campus in order to bring online services close to teachers.